Safety Citizenship Behavior: Systematic Literature Review - Anastasius Verdiansyah; Fiona Niska Dinda Nadia (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to systematically review empirical research on Safety Citizenship Behavior (SCB) over the past decade, focusing on theoretical development, methodological trends, and contextual applications. Using the PRISMA protocol, a search was conducted in the Scopus database with the keyword “Safety Citizenship Behavior” from 2014 to 2024. Fourteen eligible articles were thematically analyzed. Findings suggest that SCB is a discretionary behavior grounded in psychological motivation and social relationships that supports workplace safety. Predominant frameworks include Social Exchange Theory, Prosocial Motivation, and Mindfulness Theory. Most studies used quantitative approaches, with limited exploration of qualitative and contextual perspectives. Research was mainly conducted in construction and manufacturing sectors in Asia, with little attention to high-risk industries such as mining. This review contributes to psychology by emphasizing the role of individual agency in shaping participative safety cultures. Practical implications point to the need for leadership-driven and motivation-based interventions to foster SCB in organizational settings.